Mesopredator abundances, prey interactions and diet of Caracal caracal and Canis mesomelas in the Gamkaberg, Western Cape - Steenkamp, Elani (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.